(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
Integration of Information, Communication, and Technology (ICT) will assist teachers to the global requirement to replace traditional teaching methods with a technology-based teaching and learning tools and facilities. In Uzbekistan, ICT is considered as one of the main elements in transforming the country to the future development. A survey questionnaire was distributed randomly to the total of 101 teachers from 10 public secondary schools in Uzbekistan. The data for this quantitative research were analyzed for both descriptive and inferential statistic using SPSS (version 21) software. The results indicate that ICT integration has a great effectiveness for both teachers and the students. Findings indicate that teachers’ well-equipped preparation with ICT tools and facilities is one the main factors in success of technology-based teaching and learning. . It was also found that professional development training programs for teachers also played a key role in enhancing students’ quality learning. For the future studies, there is a need for consideration of other aspects of ICT integration especially from management point of view in regard to strategic planning and policy making.